Obstructive jaundice due to neoplastic hemobilia in a bilobed liver - Praderi, Raúl; Zerbino, Víctor; Caritat, Ricardo; Gravina, Gustavo (Cirugía del Uruguay, 2020)
1) A case of bilobated liver with permeable scissure is reported. According to the anatomical criteria it would be the fourth case in the medical literature due to persistence of sagital scissure or the first one due to persistence of left scissure. . 2) There was a short choledochus and a cancer of the gall bladder which perforated the common duct and formed a neoplastic bilio-biliary fistula. This condition is very uncommon. 3) J aundice was produced by a canalicular haemorrage, which obstructed the biliary duct and produced also a digestive haemorrage. 4) Only four previous observations of biliary obstruction due to neoplastic haemobilia have been published, and only once, like in this case, the diagnosis was performed finding neoplastic cells in the clots. 5) An haemorragic syndrome generat. ed an hemoperitoneum in aqdition to the haemobilia. 6) The p atient died eleven days after operation from acute páncreatitis and a pseudo-membranous necrotizing colitis.